2013
DOI: 10.2169/internalmedicine.52.9458
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction in Patients with Systemic Lupus Erythematosus

Abstract: Objective We aimed to define the clinical features of liver dysfunction in patients with systemic lupus erythematosus (SLE). Methods The frequency and causes of liver dysfunction were examined in 206 patients with SLE. Results Liver dysfunction was evident in 123 (59.7%) of the 206 patients. Liver dysfunction in patients with SLE can be drug-induced (30.9%) or caused by SLE itself (28.5%), fatty liver (17.9%), autoimmune hepatitis (AIH) (4.9%), primary biliary cirrhosis (2.4%), cholangitis (1.6%), alcohol (1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 20 publications
2
98
0
Order By: Relevance
“…We also examined factors associated with the response of SLE-AIH patients to treatment. SLE rarely involves the liver, but elevated liver enzymes have been reported in up to 60% of SLE patients (4)(5)(6)(23)(24)(25). Liver enzyme abnormalities in SLE patients may be caused by hepatotoxic drugs, viral hepatitis, fatty liver disease associated with steroid use, and (albeit less commonly) hepatic congestion, primary liver disease, or lupus hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined factors associated with the response of SLE-AIH patients to treatment. SLE rarely involves the liver, but elevated liver enzymes have been reported in up to 60% of SLE patients (4)(5)(6)(23)(24)(25). Liver enzyme abnormalities in SLE patients may be caused by hepatotoxic drugs, viral hepatitis, fatty liver disease associated with steroid use, and (albeit less commonly) hepatic congestion, primary liver disease, or lupus hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Hepatitis (n = 6) Minimal changes (n = 4) Normal (n = 3) Zheng et al [2] Retrospective 504 (n = 47) ↑ Total bilirubin (13%), ALT (98%), ALP (42%), GGT (49%) (n = 10) Portal blood cell infiltration (n = 8) Hydropic degeneration (n = 8) Steatosis (n = 2) Mild cholestasis (n = 2) Focal necrosis (n= 1) Nodular cirrhosis (n = 1) Takahashi et al [18] Prospective 206 (n = 123) ↑ AST, ALT (99%) ↑ ALP and GGT (81%) with exacerbations of the lupus disease, which returns to normal values after corticosteroid therapy [2,14,15] . May be a part the confusion begun in the early 50's, when AIH was wrongly referred to as "lupoid hepatitis" [11] .…”
Section: Namentioning
confidence: 99%
“…However, the prevalence reported in the literature is rather variable, with both lower [4,8,17,19] and higher [14,18,20] rate values. Zheng et al [2] also reported that the prevalence of lupus hepatitis in patients with active SLE was higher than those with inactive SLE (11.8% vs 3.2%).…”
Section: Namentioning
confidence: 99%
“…Generally, the liver is not considered to be a major target in SLE; however, 25-50% of lupus patients have abnormal liver function at some point during the disease course (Youssef and Tavill 2002;Chowdhary et al 2008;Takahashi et al 2010Takahashi et al , 2013Her et al 2011;Huang et al 2012;Bessone et al 2014). Liver dysfunction can be caused by a wide range of factors, such as drugs, steatosis, SLE itself, viral hepatitis, and comorbid autoimmune hepatitis or primary biliary cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, hepatitis B surface antigen (HBsAg)-negative patients, carrying hepatitis B surface antibody (anti-HBs) and/or hepatitis B core antibody (anti-HBc), have been considered to have achieved the resolution of HBV infection; however, the reactivation of HBV, which can cause lethal hepatitis called de novo hepatitis B, after chemotherapy, hematopoietic stem cell transplantation, or immunosuppressive therapy in patients with resolved HBV infection has been increasingly recognized (Umemura et al 2008;Urata et al 2011;Oketani et al 2012;Vassilopoulos and Calabrese 2012;Boyman et al 2014). Although previous reports indicated that the prevalence of hepatitis B was lower than that of hepatitis C in lupus patients (Chowdhary et al 2008;Takahashi et al 2010Takahashi et al , 2013Huang et al 2012), de novo hepatitis B may increase in the future because new biological agents for treating lupus patients are being introduced.…”
Section: Introductionmentioning
confidence: 99%